Application and performance of full-duplex cooperative multicast in NOMA system - Qiao WANG; Yanguo ZHOU; Xinjie YANG; Youming LI; Wei SHI; Bo CHEN (Dianxin kexue)
The application of cooperative multicast in a non-orthogonal multiple access (NOMA) system and its performances was studied where a mixed service scenario consisting of a number of the multicast users and one unicast user was employed.In such a system,a cooperative relay path selection strategy was used and a best channel conditioned multicast user was selected as relay user to relay the unicast user’s signal.The unicast user outage probability and the relay user’s capacity in closed-form were then derived.Mont Carlo simulation results validate the analysis and show that the proposed scheme significantly enhances outage probability for unicast user while maintaining the same ergodic capacity for the relay user.